2013
DOI: 10.1063/1.4807098
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical considerations for mapping activation in human cardiac fibrillation

Abstract: Defining mechanisms for cardiac fibrillation is challenging because, in contrast to other arrhythmias, fibrillation exhibits complex non-repeatability in spatiotemporal activation but paradoxically exhibits conserved spatial gradients in rate, dominant frequency, and electrical propagation. Unlike animal models, in which fibrillation can be mapped at high spatial and temporal resolution using optical dyes or arrays of contact electrodes, mapping of cardiac fibrillation in patients is constrained practically to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 40 publications
3
58
0
Order By: Relevance
“…After considerable processing and interpolation, evidence was found for rotational activity in patients with paroxysmal, persistent, and long-standing persistent AF. 564 MAPs established the minimum repolarization interval and provided physiologically feasible sequential activation paths. Movies of activation patterns and isochronal maps from individual cycles showed circulating activity around a center of rotation that was identified as rotational activity.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
See 2 more Smart Citations
“…After considerable processing and interpolation, evidence was found for rotational activity in patients with paroxysmal, persistent, and long-standing persistent AF. 564 MAPs established the minimum repolarization interval and provided physiologically feasible sequential activation paths. Movies of activation patterns and isochronal maps from individual cycles showed circulating activity around a center of rotation that was identified as rotational activity.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…Movies of activation patterns and isochronal maps from individual cycles showed circulating activity around a center of rotation that was identified as rotational activity. 564 Focal (centrifugal) activations were also identified. Both were considered drivers only if they sustained for ≥50 rotations or focal discharges.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is theoretically sufficient to map re-entry circuits in human atria whose minimum wavelength is ~4-5 cm. 22 Direct electrode contact baskets overcome many limitations inherent to other mapping methods, such as potentially unreliable signals in AF from the inverse solution, limited mapping areas by surgical plaques, and toxicity from voltage-sensitive dyes. Nevertheless, improved basket resolution and compliance characteristics would further enhance mapping.…”
Section: Wide-area Mappingmentioning
confidence: 99%
“…There has been much debate over lines -in terms of their function, where they should be placed, and if they should be created at all. Mechanistically, lines were designed to 'constrain' wavelets in human AF, but whether this is feasible is debated 75 and it has been shown that lines may interrupt localized sources 59 . A full discussion is outside the scope of this review, but since lines may be difficult to complete and incomplete lines may cause iatrogenic atrial tachycardias 12 , there is a perceptible trend towards reduced creation of lines (particularly the mitral).…”
Section: Evolving Technical Aspects Of Ablation: Less Is Morementioning
confidence: 99%